WORD WALL GAME: Students’ Vocabulary Mastery & EFL Learning - Toyibatul Koiril Yanah; Ade Ismail Ramadhan Hamid; Khusnul Khatimah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
In the development of modern learning, the use of digital media as a modern learning tool is increasingly important to encourage the effectiveness of the learning process. One of the teaching media innovations that can be used to attract students' interest in mastering the material is the Word Wall game. This study investigates the effect of the Word Wall game on students’ vocabulary mastery compared to conventional instruction, addressing the urgent need for engaging digital media to enhance English learning in secondary schools. Employing a quasi-experimental quantitative design with pretests and posttests, the research involved 40 eighth-grade students at MTs Muhammadiyah 1 Samarinda in the 2024/2025 academic year, selected through purposive sampling. The experimental group received vocabulary instruction using the Word Wall game, while the control group followed traditional methods. Results show substantial improvement in the experimental class (pretest 56.50; posttest 82.50) compared to the control group (pretest 58.00; posttest 68.50). The independent t-test yielded a significance value of 0.001, indicating a statistically significant effect of the Word Wall game. This study contributes evidence that digital game-based media can effectively support vocabulary acquisition. However, the limited sample suggests the need for broader and longitudinal research.